Shakespearean sensations : experiencing literature in early modern England - Craik, Katharine A.; Pollard, Tanya (Cambridge University Press, 2013)
"This strong and timely collection provides fresh insights into how Shakespeare's plays and poems were understood to affect bodies, minds and emotions. Contemporary criticism has had surprisingly little to say about the early modern period's investment in imagining literature's impact on feeling. Shakespearean Sensations brings together scholarship from a range of well-known and new voices to address this fundamental gap. The book includes a comprehensive introduction by Katharine A. Craik and Tanya Pollard and comprises three sections focusing on sensations aroused in the plays; sensations evoked in the playhouse; and sensations found in the imaginative space of the poems. With dedicated essays on Hamlet, Macbeth, Othello and Twelfth Night, the collection explores how seriously early modern writers took their relationship with their audiences and reveals new connections between early modern literary texts and the emotional and physiological experiences of theatregoers"--